Impact of the 5A nursing model on immune balance and lymph node metastasis in primary liver cancer patients post-CyberKnife treatment - Xin Su; Xiuli Li; Juan Zhang; Haixian Fang; Liwei Zhang; Li He (BMC Cancer)
Abstract Objective The study aimed to investigate the impact of the 5A nursing model on immune status, lymph node metastasis, and survival in patients with primary liver cancer following CyberKnife treatment. Methods A total of 80 patients diagnosed with primary liver cancer and admitted to the Oncology Department of our hospital between February and December 2023 were enrolled. All patients underwent tissue biopsy confirmation and were scheduled to receive CyberKnife treatment. Patients were randomly assigned to either the 5A nursing group or the conventional nursing group, with 40 patients in each group. Written consent was obtained from all participants upon enrollment. Baseline data for both groups were recorded. Tumor tissue immune cell infiltration was assessed using flow cytometry. Levels of IL-2, IL-10, and TNF-α cytokines in serum were measured via ELISA. Lymph node metastasis occurrence was compared between groups during follow-up. Patient quality of life was evaluated using the EORTC QLQ-C30 survey. Progression-free survival (PFS) and OS were assessed and compared between groups. Results Baseline characteristics, including age, gender, pathological stage, lymph node metastasis, and underlying disease, were similar between the two groups (P > 0.05). In the 5A nursing group, concentrations of CD8 + T cells and NK cells were higher compared to the conventional nursing group (P < 0.05), whereas Tregs cell concentration was lower in the 5A nursing group than that in the conventional nursing group (P < 0.05). Levels of IL-2 and TNF-α were elevated in the 5A nursing group compared to those in the conventional nursing group (P < 0.05), while IL-10 levels were decreased in the 5A nursing group (P < 0.05). During the initial 6 months, the rate of lymph node metastasis did not significantly differ between the two groups (P > 0.05). However, at the 12th and 18th months, lymph node metastasis incidence was lower in the 5A nursing group compared to the conventional nursing group (P < 0.05). The 5A nursing group also demonstrated higher quality of life scores compared to the conventional nursing group (P < 0.05). PFS and OS were significantly longer in the 5A nursing group compared to the conventional nursing group (P < 0.05). Conclusion The 5A nursing model significantly impacts immune balance and reduces lymph node metastasis in primary liver cancer patients following CyberKnife treatment. This model enhances CD8 + T cell and NK cell concentrations while reducing Tregs cells, thereby promoting a stronger anti-tumor immune response and ultimately decreasing the rate of lymph node metastasis.